PERUBAHAN TRADISI JEMPUT ANTAR DI DALAM PERNIKAHAN ADAT MELAYU DI DESA KOTO BARU KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Rahmadany, Nur Syabrina; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Marriage is a very sacred procession for everyone. There are many stages that every couple must go through if they want to get married. One of the stages that will be passed is the stanges of costums in the village of Koto Baru. The purpose of this study was to of the pick-up and drop off tradition in the wedding procession in vilage of Koto Baru, singingi HilirDistrict, Kuantan Singingi Regency. The method used qualitative method. Data collection uses observation an in-def interviews, as well as documentation. The result of study are the conditions in Jemput Antar the sguttle procession must have tribes in Koto Baru Village. If the groom comes from outside the village of Koto Baru then the groom must do pulang bainduak, do not perform same tribe, not doing siri marriage, must use a ring soko or ring kosek ancestral legacy. Main factor causing change tradition is economic, era modern times, so prefer seserahan. Key words : pick-up tradition, costum change, cause tradision doesn’t work